Efektivitas Media Leaflet dan Video pada Tingkat Pengetahuan tentang Tanda Bahaya Masa Nifas - Masini Masini; Wahyu Pujiastuti; Herlina Tri Damailia; Ribkha Itha Idhayanti; Rubiyana Islam Kartini (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
The puerperium is a vital time for both mothers and newborns, marked by a heightened risk of complications, especially within the first 24 hours after delivery. This research aimed to assess the impact of health education through video media on increasing postpartum mothers' knowledge of puerperium danger signs at the Bunda Parakan Temanggung Clinic. A quasi-experimental design with a non-equivalent control group was used, involving 30 postpartum mothers selected via accidental sampling. Data were gathered through pre- and post-intervention questionnaires, with both video and leaflet media used as educational tools, and analyzed with a t-test. The results showed that video media significantly enhanced mothers' knowledge, with 67% of respondents showing adequate understanding (p-value 0.003, mean difference 0.67), compared to 53% for the leaflet group (p-value 0.014, mean difference 0.46). These outcomes suggest that video media is more effective than leaflets in raising awareness about puerperium danger signs, and thus, it is advised that health education programs emphasize the use of video media to better inform postpartum mothers